2001
DOI: 10.1021/np000372l
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anti-HIV Macrocyclic Peptide from Palicourea condensata

Abstract: A 37 amino acid cyclic polypeptide has been isolated from the organic extract of the tropical tree Palicourea condensata. Palicourein (1) is the largest of a growing family of plant peptides that contain a cyclized amino acid backbone cross-linked via three internal disulfide bridges. Palicourein inhibits the in vitro cytopathic effects of HIV-1RF infection of CEM-SS cells with an EC50 value of 0.1 microM and an IC50 value of 1.5 microM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 14 publications
0
106
0
1
Order By: Relevance
“…Cyclotides can also be found in plants of a second family, namely the Rubiaceae. However, for this family the literature seems to suggest that in some species cyclotides are only expressed in woody parts, such as the bark (Gustafson et al, 1994;Bokesch et al, 2001).…”
Section: Discussion Cyclotide Expression and Biosynthesismentioning
confidence: 99%
“…Cyclotides can also be found in plants of a second family, namely the Rubiaceae. However, for this family the literature seems to suggest that in some species cyclotides are only expressed in woody parts, such as the bark (Gustafson et al, 1994;Bokesch et al, 2001).…”
Section: Discussion Cyclotide Expression and Biosynthesismentioning
confidence: 99%
“…Loop 6 is formed at the cyclization point of the linear precursor. References for the listed cyclotides are as follows: cycloviolin C (Hallock et al, 2000), varv A (Claeson et al, 1998), Hypa A (Broussalis et al, 2001), cyclopsychotride (Witherup et al, 1994), circulin A (Derua et al, 1996), palicourein (Bokesch et al, 2001), and kalata B1 (Saether et al, 1995). A ribbon diagram of the cyclotide framework based on the structure of kalata B1 (PDB ID 1NB1) with the cystine knot core rendered and numbering of loops is shown in the middle of the figure.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that both peptides exhibited IC 50 values that were 5.0 μM when directed against cell lines of lymphoma (U-937 GTB) colorectal cancer (Ht116) and colonadeno carcinoma (HT29) that were generally comparable to that of doxorubicin [62,63], a well-established anticancer drug [64]. Other AHDPs from plants of the Rubiaceae, include palicourein (net charge -1), from the tropical plant, Palicourea condensate [65], and chaC1 (net charge -1), which was recently discovered in Chassalia chartacea [66]. These peptides were found to have potent activity against cell lines of cervical cancer (HeLa) and acute lymphoblastic leukaemia (CEM-SS) with IC 50 values of 1.5 μM and 9.8 μM, respectively [66,67].…”
Section: Ahdps From Cyclotidesmentioning
confidence: 99%
“…However, based on structural differences in their molecular framework, cyclotides can be divided into a number of groups [41,42], including two major subfamilies, generally known as the Möbius and bracelet peptides (Fig. 4) [15,77], and a much smaller group termed chimeric cyclotides [65]. The Möbius and bracelet subfamilies have fundamentally different molecular architectures that are primarily distinguished by the presence of a conserved proline residue in cis conformation in loop 5 of the former subfamily, causing a 180° twist in the loop, which is not seen in the latter subfamily [15,77].…”
Section: Ahdps From Cyclotidesmentioning
confidence: 99%
See 1 more Smart Citation